Diversity? Great for Most Just Less So for Me: How Cognitive Abstraction Affects Diversity Attitudes and Choices - Claudia Toma; Ashli B. Carter; Katherine W. Phillips (Behavioral Sciences)
Individuals’ decisions to promote or limit diversity in the workplace are ambivalent and may be influenced by their cognitive focus. Drawing from construal level theory, we test across five studies whether individuals are more supportive of diversity when diversity is thought of more abstractly versus concretely. Furthermore, we examined the salience of diversity pros and cons as the underlying mechanisms, as well as the role of egalitarian beliefs as a boundary condition for this discrepancy. We tested these hypotheses in five studies, which varied in samples, cognitive focus manipulation, and measures. Dutch and American individuals indicated more positive attitudes toward diversity (Studies 1 and 2) and made more choices that enhanced diversity (Studies 2 and 5) when they considered diversity abstractly (for most companies and teams) rather than concretely (for their own company and teams). Furthermore, the discrepancy in diversity attitudes by construal level was more pronounced among individuals with egalitarian beliefs (Study 3) and was driven by the heightened salience of diversity pros at more abstract versus concrete levels of construal (Study 4). This research contributes to further understanding the ambivalent view of diversity and provides concrete recommendations for diversity management in organizations.